2016
DOI: 10.1107/s205979831601723x
|View full text |Cite
|
Sign up to set email alerts
|

The N14 anti-afamin antibody Fab: a rare VL1 CDR glycosylation, crystallographic re-sequencing, molecular plasticity and conservativeversusenthusiastic modelling

Abstract: Models of the VL1 glycosylated Fab fragment independently refined from two non-apparent (pseudo) isomorphous crystals show significant differences, allowing the meaning of accuracy in structure description to be revisited, while at the same time inviting reflections about the benefits and boundaries of complex solvent modelling and validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 79 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…However, a number of depositors have reported that the LLDF-based classification marks ligands with reasonable electron-density fit as 'outliers' (private communications), and Naschberger et al (2016) note that LLDF misclassifies reasonably placed solvent molecules such as PEG fragments and glycans. To assess whether these problems are isolated or are more general, an analysis of the LLDF-based classification and the RSCC 'rule of thumb' was undertaken for all PDB ligands where the VR includes both values (Table 1).…”
Section: Assessing Ligand Fit To Electron Densitymentioning
confidence: 99%
“…However, a number of depositors have reported that the LLDF-based classification marks ligands with reasonable electron-density fit as 'outliers' (private communications), and Naschberger et al (2016) note that LLDF misclassifies reasonably placed solvent molecules such as PEG fragments and glycans. To assess whether these problems are isolated or are more general, an analysis of the LLDF-based classification and the RSCC 'rule of thumb' was undertaken for all PDB ligands where the VR includes both values (Table 1).…”
Section: Assessing Ligand Fit To Electron Densitymentioning
confidence: 99%
“…These challenges were adequately addressed . In fact, the challengers confirmed the correctness of the electron density for the bound ligand and also used the aforementioned arguments regarding plasticity while interpreting antibody glycosylation at relatively high B ‐factors and lower σ cut‐off in an independent antibody structure . They emphasized that the difference electron density omit maps should be viewed at a minimum of 3.0 σ because the default contour level to view such maps in Coot is 3.0 σ .…”
Section: Challenging Publications Involving Structural Datamentioning
confidence: 95%
“…7 does amplify the concerns that a single-crystal structure, particularly in a restrictive crystal packing, may not be sufficient as a basis for a drug-lead discovery study (Dym et al, 2016). The power of multiple crystal forms to explore the conformational space of a protein in its native solvent environment has repeatedly been made (see, for example, Naschberger et al, 2016). Given modern high-throughput crystallography methods, as many different crystal forms should be examined as possible in order to obtain a complete picture, particularly in the case of highly promiscuous small-molecule and drug transporters, as exemplified by human albumin and afamin.…”
Section: Contextual Flexibility Affects Binding-site Analysismentioning
confidence: 99%